The Effect of Excellent Service and Product Quality on Consumer Satisfaction at Mejablay Rengasdengklok - Fathma Putri Nabila; Aji Tuhagana; Zenita Apriani (International Journal of Economics and Management Research, 2025)
Food business in Indonesia, especially in the food sector, faces very tight competition. Sellers need to understand how to satisfy customers in order to maintain their position in the market. By recognizing the steps needed to achieve customer satisfaction, they can influence and convince customers to choose their products. Customer satisfaction with a product or service is very important for sellers, because it is an indicator of their success. Spicy food is now very popular, especially among Indonesian people. The purpose of this study is to investigate how customer happiness is impacted by location and excellent service. Mie Jablay, located in South Rengasdengklok, Karawang, was the site of the study. In order to gather data, 96 Mie Jablay clients were given questionnaires as part of a quantitative technique. Techniques from scale analysis and multiple linear regression were used in the analysis. The category "Stimme Zu" successfully reflected high levels of customer happiness, product quality, and service, according to the results of descriptive analysis. Customer satisfaction at Mie Jablay Rengasdengklok is greatly impacted by both outstanding customer service and product quality, whether evaluated separately or in tandem, according to the verification analysis's findings.